1999
DOI: 10.1164/ajrccm.160.1.9810082
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Prevention in Methadone Maintenance Clinics

Abstract: To determine the effectiveness and cost-effectiveness of a program to provide screening for tuberculosis infection and directly observed preventive therapy (DOPT) in methadone maintenance clinics, we determined completion rates of screening for tuberculosis infection, medical evaluation, and preventive therapy, as well as the number of active tuberculosis cases and tuberculosis-related deaths prevented, in five clinics in San Francisco, California. Between 1990 and 1995, a total of 2,689 clients (of whom 18% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…INH completion in the routine care group was 13.1%, even lower than the 26% found among homeless clients at the same TB clinic by Tulsky et al (2000). Likewise, INH completion rates in the methadone groups were lower than in uncontrolled studies in methadone maintenance clinics that reported completion rates of 80-90% (Gourevitch et al, 1996;Gourevitch et al, 1998;Snyder et al, 1999).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…INH completion in the routine care group was 13.1%, even lower than the 26% found among homeless clients at the same TB clinic by Tulsky et al (2000). Likewise, INH completion rates in the methadone groups were lower than in uncontrolled studies in methadone maintenance clinics that reported completion rates of 80-90% (Gourevitch et al, 1996;Gourevitch et al, 1998;Snyder et al, 1999).…”
Section: Discussioncontrasting
confidence: 55%
“…A randomized trial studying the impact of location of tuberculosis screening showed that chest radiograph completion by drug users was much higher in a methadone clinic than in a nearby medical clinic (86% vs. 23%) (Umbricht-Schneiter et al, 1994). Completion rates for directly observed INH have been as high as 80-90% in methadone programs (O'Connor et al, 1992;Gourevitch et al, 1998;Snyder et al, 1999), regardless of participants' drug use (Gourevitch et al, 1996). This contrasts with other settings, where TB medication adherence among substance users has been lower than among non-users (Combs et al, 1990), even with direct observation (Burman et al, 1997;Pablos-Maendez et al, 1997;Perlman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Drug abuse treatment, particularly opioid agonist regimens such as methadone maintenance are effective in reducing the frequency of injection drug use, and subsequently, the incidence of HIV infection (Metzger and Navaline, 2003) and tuberculosis (Snyder et al, 1999). Since only 15-20% of IDUs are enrolled in a drug treatment program at any given time in the U.S. (Metzger and Navaline, 2003), increasing the number and proportion of drug users in treatment is an important public health goal.…”
Section: Introductionmentioning
confidence: 99%
“…In one study of patients with latent TB infection (LTBI), providing MMT with onsite DOT was associated with a four-fold improvement of isoniazid preventive treatment (IPT) completion (Batki, Gruber, Bradley, Bradley, & Delucchi, 2002). In another New York-based study, providing IPT for LTBI and DOT in MMT programs in the U.S. has been shown to be both an effective (Gourevitch, Wasserman, Panero, & Selwyn, 1996) and cost-effective TB prevention intervention (Snyder et al, 1999) among PWIDs. Description of TB treatment for patients receiving and not receiving MMT, aside from a small sample (N = 12) in the U.S. (Gourevitch et al, 1996), has not been empirically assessed until now.…”
Section: Discussionmentioning
confidence: 99%